Statistical Analysis of the Factors Affecting the Recovery of Microbial Oil - BRAHMANI PRIYADARSHINI, S.R.; MISHRA, M.C.; MURUGAN, V.; ANGELIN, THANGA (Asian Journal of Chemistry, 2010)
Production of microbial oil by fermentation process using oleaginous organisms is one of the potential alternative sources of collecting lipids. Rhodotourula gracilis, is one of the oleaginous yeast, explored for their oleaginiecity. The degradation of the cell wall of the yeast is an absolute necessity in order to extract oil using organic solvents. Acid hydrolysis is one of the chemical methods commonly employed for this purpose. The concentration, contact time and temperature of acid hydrolysis are the three variable parameters observed during degradation of the cell wall. An analysis of variance of these three factors was carried out to analyze to know which of the three factors affected the extraction of oil significantly and also to know the interaction between these factors.